An Overview of the Western African Response to the International Counter-terrorism Legal Framework - Mylonaki, Emmanouela (Pécs journal of international and European law, 2015)
Terrorism is a phenomenon treating peace and security worldwide and is not a new phenomenon affecting many countries in West Africa. As such it affects the interests of the international community, calling not only for international action but also for the response of African States. The response of Western African States to the existing international counter-terrorism legal framework is the subject matter of the present article. It is not the aim of the article to provide a detailed account of African States responses but to provide an overview of the reaction of West Africa to the existing counter terrorism framework evident through UN action. In order to provide such an overview the article presents the existing international legal framework before it outlines the response of West African States to this framework.